EFFECT OF SATISFACTION OF BENEFITS TO CONTIUNANCE COMMITMENT AND INTENTION TO LEAVE IN HOSPITAL DENPASAR CITY - Purnama Putra, Ida Bagus Putu; Supartha, I Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.12.TAHUN 2018DO - 10.24843/EEB.2018.v07.i12.p01, 2018)
The reward satisfaction is the point determinant towards continuance commitment and employee's desire to leave the organization. This research has aims to determine the influence of reward satisfaction and commitment continuance with the desire to leave from the organization. Apply with 103 samples from 138 non-paramedic employees in the General Hospital in the city of Denpasar. The Data Analyzed by Structural Equation Modeling (SEM) using smart PLS.             The results of the research Showed that reward satisfaction had a significant influence positive effect to the continuance commitment and significant negative to the employee's desire to leave from the organization. Thereby, continuance commitment has a significant negative influence to the employee's desire to leave the organization. The implication of this research is to reduce the level of employee's desire leave from organization to increase of reward satisfaction and then continuance commitment will increase.